Perlindungan Hukum Terhadap Konsumen Atas Penarikan Obat Sirup Berbahaya di Kecamatan Pangkalan Kerinci - Situmorang, Agnes Fernadesta; Ismi, Hayatul; Dasrol, Dasrol (Journal of Health Education Law Information and Humanities, 2025)
The Some consumers choose to have limited knowledge about the fairness of the quality and price of goods/services. In the Law on Consumer Protection, there are several articles that regulate the prohibited acts for business actors, the obligations of business actors, and the rights of consumers. However, the problem is not only limited to the responsibility of drug stores, but there must be legal protection efforts for consumers who experience acute indigestion as a result of consuming dangerous syrup. The formulation of the first problem is how is the legal protection of consumers over the withdrawal of dangerous syrup in Pangkalan Kerinci District, secondly how is the responsibility of drug stores as business actors in providing legal protection to consumers over the withdrawal of dangerous syrup in Pangkalan Kerinci District. The research method in this thesis uses a type of sociological legal research, namely research on the effectiveness of laws that live in society. The data collection technique in this research is the interview method and literature review. Then after the data is collected, it is analyzed to draw conclusions. The research method in this thesis uses a type of sociological legal research that seeks truth in field facts. The result of the research is that legal protection against the withdrawal of dangerous syrup shows the importance of legal protection for consumers, especially in terms of safety and health. The Consumer Protection Law provides a strong legal basis to ensure consumer rights are protected, including in the case of dangerous drug recalls. If the syrup sold proves to be dangerous or contains unsafe ingredients, consumers are entitled to compensation or return of goods, as well as transparent information about the drug recall process. The responsibility of drug stores as business actors in providing legal protection to consumers for the withdrawal of dangerous syrup in Pangkalan Kerinci District such as compensation in the form of a refund or exchange of safe products. In this case, based on policies and procedures, business actors, namely drug stores can provide compensation in accordance with the losses suffered by consumers. In this study, it can be concluded that drug stores do not provide compensation or compensation money to consumers who come to return dangerous syrup drugs that have been withdrawn from circulation.